2009
DOI: 10.1111/j.1478-3231.2008.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal monocyte Human leukocyte antigen‐DR expression is a prognostic marker in critically ill patients with decompensated liver cirrhosis

Abstract: Here we establish the relative HLA-DR expression (admission/day 3) as a prognostic marker for ICU mortality in critically ill cirrhotic patients. These results may guide the evaluation of immune-modulating therapies in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 27 publications
5
46
2
Order By: Relevance
“…A bilirubin level of >3.2 mg/dl and platelet count of <98 000/mm 3 significantly increase the likelihood of SBP,53 and each model for end-stage liver disease (MELD) point increases the risk of SBP by about 11% 54. However, circulating mononuclear cells also present with alterations in Toll-like receptor (TLR)55 and HLA expression56 57 as well as reduced chemotactic, opsonic, phagocytic and killing capacity 58 59. Furthermore, genetic variants influencing host defence mechanisms such as CARD15/NOD231 60 and TLR261 have been reported to be associated with an enhanced probability of acquiring SBP.…”
Section: Epidemiology and Prognosis Of Sbpmentioning
confidence: 99%
“…A bilirubin level of >3.2 mg/dl and platelet count of <98 000/mm 3 significantly increase the likelihood of SBP,53 and each model for end-stage liver disease (MELD) point increases the risk of SBP by about 11% 54. However, circulating mononuclear cells also present with alterations in Toll-like receptor (TLR)55 and HLA expression56 57 as well as reduced chemotactic, opsonic, phagocytic and killing capacity 58 59. Furthermore, genetic variants influencing host defence mechanisms such as CARD15/NOD231 60 and TLR261 have been reported to be associated with an enhanced probability of acquiring SBP.…”
Section: Epidemiology and Prognosis Of Sbpmentioning
confidence: 99%
“…The poorer outcome in the patients whose CRP levels failed to improve leads us to hypothesise inability to resolve inflammation may be pathophysiologically important in this syndrome. It has recently been shown that decreased HLA-DR expression [45] and a further decrease over three days is noted in non-survivors, whereas survivors showed increased or at least unchanged HLA-DR levels [46]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, a genetically dependent increased production of IL-10 is strongly associates with active lesions of cutaneous leishmaniasis (213). IL-10 also plays a decisive role in the formation of immune paralysis, a temporary immunodeficiency occurring after trauma, major surgery, burns, or shock, and which has a high risk of bacterial/mycological infections with lethal outcomes (214)(215)(216)(217)(218)(219). It seems that macrophagederived IL-10 is also jointly responsible for age-associated immune deficiency (220).…”
Section: Role Of Il-10 In Immune-mediated Diseasesmentioning
confidence: 99%